Breed related odds ratio and anatomic distribution of canine mast cell tumours in Austria - Leidinger, E. F.; Freeman, K.; Kirtz, G.; Hooijberg, E. H.; Sick, K. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2014)
Objective: An increased risk of mast cell tumours (MCT) in certain breeds has been described repeatedly in the literature. The incidence of MCTs for registered breeds in Austria, an estimate of the risk by means of the odds ratios based on breed as well as the anatomic localisation of MCTs were examined. Material and methods: In the first part of the study, the ranking of breeds in Austria based on 147,802 dogs with known breed (including mixed breed) was determined, based on those dogs included in the laboratory data base from 2000 to 2010. In the second part of the study, 476 dogs were identified with MCTs and analysed by age, sex, Patnaik grade of MCT and breed distribution. The odds ratios with confidence intervals were calculated for all breeds with skin tumours. Results: The age distribution showed a peak in the age group from 6.1 to 8.0 years; 70% of MCTs were localised to the head and trunk. No significant difference was found based on gender. The evaluation of the odds ratios showed that only four of the 20 of the most popular in Austria breeds (Boxer, Bernese Mountain Dog, Golden Retriever, Spaniel) had an increased risk; on the other hand, some breeds which have not been previously identified in the literature were indicated to have a significantly increased risk for MCT (e.g., Dogo Argentino, Tibetan Spaniel, Pyrenean Mountain Dog, Beauceron, and Austrian Smooth-haired Hound). Conclusion and clinical relevance: Because disease risk may influence the popularity of some currently rare breeds, consultation with breeders and owners regarding the identification of the breeds newly identified in this study as an increased risk for development of mast cell tumours is indicated.
Keywords: Dog breed; risk; mastocytoma; cytology; histopathology